New approach methodologies (NAMs) for improved developmental and reproductive toxicity (DART) assessment with focus on endocrine disruption – a PARC project - Ardenkjær-Skinnerup, Jacob; Baert, Yoni; Bajard, Lola; Blum, Jonathan; Brion, François; Coppola, Lucia; Fini, Jean-Baptiste; Fritsche, Ellen; Holbech, Henrik; Hurem, Selma; Jacobs, Miriam Naomi; Johansson, Hanna Katarina Lilith; et al. (Frontiers in Toxicology, 2026)
Endocrine disruptors (EDs) are implicated in adverse developmental and reproductive outcomes, yet their identification remains a major challenge in chemical safety assessment. Current testing strategies rely heavily on animal models, which are constrained by ethical concerns, interspecies differences, and limited mechanistic resolution but justified by the complexity of the endocrine system and its physiology. Capturing the complex biology of intact organisms and incorporating toxicokinetic properties in alternative test methods is challenging. To address this, the European Partnership for the Assessment of Risks from Chemicals (PARC) is advancing the development and regulatory integration of new approach methodologies (NAMs). This project specifically contributes by developing and validating human-relevant NAMs to identify key aspects of endocrine disruption relevant to developmental and reproductive toxicity (DART). Key innovative activities include predictive modeling, refinement of zebrafish and amphibian embryo assays, and establishment of advanced in vitro systems for assessing toxicity in the oocyte, testis, placenta, and brain. By combining mechanistic insights with multi-modality and high throughput testing strategies, this work aims to improve the predictive power and regulatory utility of NAMs for ED identification within the One Health paradigm.